Internet search algorithms: use of metadata, literacy and algorithmic education in the human–computer interaction - Barragán-Perea, Efraín Alfredo; Tarango, Javier (Digital library perspectives, 2024)
Purpose This paper aims to identify alternatives for citizens to get out of the bubble when interacting with the information provided by the internet through search engines. This situation arises because there is extensive ignorance about the way search engines operate and the way advanced search algorithms operate, both situations based on the specific segmentation of the public, which creates difficulties in obtaining vast information that allows the contrast and development of diverse perspectives, which do not necessarily lead to the use of critical thinking. Design/methodology/approach To achieve this contribution, a documentary-type investigation was carried out based on the review of the scientific literature on the subject, and the nature of this investigation, due to its purpose, being descriptive. The study takes as document selection criteria those original articles whose content relevance is linked to the purposes of this research proposal, published in scientific databases (SciELO, RedAlyC, Dialnet, ScienceDirect, WoS and Scopus) mostly between the years 2018 and 2023, in Spanish and English, that described the impact of bubble filters on full access to information and data privacy, for which the topics were addressed: internet search algorithms, bubble filters, search engines, privacy policies in search engines and management of personal data. Findings At the beginning, this paper clarifies the concepts of search algorithms on the Internet, bubble filters, search engines and privacy policies in search engines, which made it possible to identify alternatives that would allow the user to face the silent reality of the algorithms and avoid the bias in the information that the algorithm provides, in addition, the need to generate algorithmic literacy mechanisms, training in the use of metasearch engines and education in algorithms is proposed, with which citizens can exercise critical thinking in the way they interact on the internet. Research limitations/implications This is a theoretical proposal, in which various inferences are made from theoretical knowledge without fieldwork. Originality/value It is considered a document of important value in the training processes of librarians and information professionals in the training of users and in the ways of interaction with technology.